Mechanism of carbonate assimilation by intraplate basaltic magma and liquid immiscibility: example of Wangtian’e volcano (Changbaishan volcanic area, NE China) - Andreeva, Olga A.; Dubinina, Elena; Andreeva, Irina A.; Yarmolyuk, Vladimir V.; Bychkov, Andrey; Borisova, Anastassia; Ji, Jianqing; Zhou, Xin; Kovalchuk, Elena V.; Borisovsky, Sergey Y.; Averin, Alexey A. (Frontiers in Earth Science, 2023)
The balance of CO2 during abundant basaltic magma production is an important factor of volcanic hazards and climate. In particular, this can be explored based on CO2-rich mantle-derived magmas or carbonate assimilation by basaltic melts. To reconstruct the origin of Fe-rich carbonates hosted by Cenozoic basalts from Wangtian’e volcano (northeast China), we studied elemental compositions of melt, crystalline and fluid inclusions in magmatic minerals as well as the oxygen and carbon isotope compositions of the plagioclase and carbonates from basalts. The crystallization of basaltic magmas occurred in shallow chamber (∼4 km) at temperatures of 1,180°C–1,200°C and a pressure of 0.1 ± 0.01 GPa. Stable Fe-rich carbonates occur in the Wangtian’e tholeiite basalts as groundmass minerals, crystalline inclusions in plagioclase and globules in melt inclusions, which suggests that they crystallized from a ferrocarbonate melt. The values of δ18О and δ13С in the minerals analyzed by laser fluorination method are in line with the sedimentary source of Fe-rich carbonates, indicating assimilation and partial decomposition of carbonate phases. The parent ferrocarbonate melt could be produced during interactions between the basaltic magma and the crustal marbles. The phase diagram and thermodynamic calculations show that the ferrocarbonate melt is stable at a temperature of 1,200°C and a pressure of 0.1 GPa. Our thermodynamic calculations show that carbonate melt containing 73 wt% FeCO3, 24 wt% MgCO3 and 3 wt% CaCO3 is in thermodynamic equilibrium with silicate melt in agreement with our natural observations. The proposed mechanism is crustal carbonate sediment assimilation by the intraplate basaltic magma resulting in the melt immiscibility, production of the ferrocarbonate melt and the following Fe-rich carbonate mineral crystallization during magma residence and cooling.